2006
DOI: 10.1104/pp.106.080069
|View full text |Cite
|
Sign up to set email alerts
|

The SCABRA3 Nuclear Gene Encodes the Plastid RpoTp RNA Polymerase, Which Is Required for Chloroplast Biogenesis and Mesophyll Cell Proliferation in Arabidopsis

Abstract: In many plant species, a subset of the genes of the chloroplast genome is transcribed by RpoTp, a nuclear-encoded plastidtargeted RNA polymerase. Here, we describe the positional cloning of the SCABRA3 (SCA3) gene, which was found to encode RpoTp in Arabidopsis (Arabidopsis thaliana). We studied one weak (sca3-1) and two strong (sca3-2 and sca3-3) alleles of the SCA3 gene, the latter two showing severely impaired plant growth and reduced pigmentation of the cotyledons, leaves, stem, and sepals, all of which we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
146
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 136 publications
(150 citation statements)
references
References 104 publications
4
146
0
Order By: Relevance
“…This suggested function is not supported by our previous study demonstrating that RpoTm and RpoTmp genes exhibit fully overlapping expression patterns in different tissues and at different developmental stages in Arabidopsis (Emanuel et al, 2006). From a phenotypical comparison of RpoTp-defective, RpoTmp-defective, and double mutant plants, Hricova et al (2006) concluded RpoTp and RpoTmp to have redundant functions in plant development.…”
Section: Evolutionary Diversification Of Transcriptional Properties Omentioning
confidence: 41%
“…This suggested function is not supported by our previous study demonstrating that RpoTm and RpoTmp genes exhibit fully overlapping expression patterns in different tissues and at different developmental stages in Arabidopsis (Emanuel et al, 2006). From a phenotypical comparison of RpoTp-defective, RpoTmp-defective, and double mutant plants, Hricova et al (2006) concluded RpoTp and RpoTmp to have redundant functions in plant development.…”
Section: Evolutionary Diversification Of Transcriptional Properties Omentioning
confidence: 41%
“…1 E and F). Mutation of a nuclearencoded, plastid-targeted RNA polymerase SCABRA 3 (SCA3) (32), which is required for chloroplast biogenesis and has an indirect impact on carotenoid content, also showed similarly reduced LR capacity ( Fig. 1 E and F).…”
Section: Resultsmentioning
confidence: 97%
“…However, only two genes (RPOTp and RPOTm) have been detected in monocotyledons (4,7,8), thus raising the question of the function of RPOTmp in plastids of dicotyledon plants. Recent results have shown that RPOTp can be regarded as the principal NEP enzyme in chloroplasts playing an important role in chloroplast transcription, biogenesis, and mesophyll cell proliferation (9,10). Results obtained with RPOTmp indicate partial replacement of RPOTp in RPOTp mutants (10,11), an early function in lightinduced accumulation of several plastid mRNAs (12,13), and specific transcription of the rrn operon of Arabidopsis from the PC promoter during seed imbibition and germination (10).…”
mentioning
confidence: 80%